2020
DOI: 10.1111/den.13618
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of endoscopic submucosal dissection using a scissors‐type knife with prophylactic over‐the‐scope clip closure for superficial non‐ampullary duodenal epithelial tumors

Abstract: Background and study aim This study aimed to assess the safety and feasibility of endoscopic submucosal dissection (ESD) using a scissors‐type knife with prophylactic closure using over‐the‐scope clip (OTSC) for superficial non‐ampullary duodenal epithelial tumors (SNADETs). Patients and methods Consecutive patients who underwent ESD for SNADETs >10 mm between January 2009 and July 2019 were retrospectively enrolled. We performed ESD using either a needle‐type knife (Flush Knife‐ESD) or a scissors‐type knife (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 31 publications
(42 reference statements)
1
92
0
Order By: Relevance
“…In ESD-S, the scissor-type knife allows the operator to con rm the cutting line after grasping the tissue; if the muscle layer is grasped accidentally, it can be released prior to cutting, thereby preventing muscle injuries. A previous study also reported lower complication rates in ESD-S as compared to in ESD-N [28]. ESD-S offers an advantage in that experts can con rm the cutting line while teaching the ESD procedure to trainees.…”
Section: Discussionmentioning
confidence: 80%
“…In ESD-S, the scissor-type knife allows the operator to con rm the cutting line after grasping the tissue; if the muscle layer is grasped accidentally, it can be released prior to cutting, thereby preventing muscle injuries. A previous study also reported lower complication rates in ESD-S as compared to in ESD-N [28]. ESD-S offers an advantage in that experts can con rm the cutting line while teaching the ESD procedure to trainees.…”
Section: Discussionmentioning
confidence: 80%
“…Third, we did not compare the outcome of D‐LECS and ESD alone in this study. Recently, the efficacy for preventing perforations after duodenal ESD using endoscopic over‐the‐scope clip and string clip was reported 8–10 . Dohi et al 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the efficacy for preventing perforations after duodenal ESD using endoscopic over‐the‐scope clip and string clip was reported 8–10 . Dohi et al 10 . reported a low incidence of 1.8% delayed perforation rate after duodenal ESD with the over‐the‐scope clip.…”
Section: Discussionmentioning
confidence: 99%
“…We incised the mucosa and dissected the submucosal layer using the pocket-creation method with a scissors-type knife (Clutch Cutter; Fujifilm Co, Ltd, Tokyo, Japan), as described previously. 4 We created 2 oral-to-anal submucosal tunnels on the sides of the anterior and posterior walls (Fig. 5).…”
mentioning
confidence: 99%